2017
DOI: 10.14744/nci.2017.60590
|View full text |Cite
|
Sign up to set email alerts
|

Vitelline duct pathologies in neonates

Abstract: OBJECTIVE:The aim of this study was to review the management of pediatric cases of vitelline duct pathology (VDP) detected surgically or incidentally during the neonatal period and the outcomes.METHODS:The data of newborns who were symptomatic and underwent VDP resection or who were incidentally diagnosed with VDP at a single institution between 1985 and 2015 were retrospectively analyzed in terms of age, sex, clinical features, treatment, perioperative findings, ectopic tissue pathology, and postoperative fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…A similar demographic profile was also noted by other studies. 4,11,12 Among the VID anomalies, Meckel's diverticulum was the commonest accounting for 75% of the cases in our study. A similar study reported 67% of their symptomatic VID remnant cases to be Meckel's diverticulum.…”
Section: Discussionmentioning
confidence: 58%
“…A similar demographic profile was also noted by other studies. 4,11,12 Among the VID anomalies, Meckel's diverticulum was the commonest accounting for 75% of the cases in our study. A similar study reported 67% of their symptomatic VID remnant cases to be Meckel's diverticulum.…”
Section: Discussionmentioning
confidence: 58%
“…8 In another review of 36 neonates with vitelline duct pathologies, there were 11 cases of patent vitelline duct, and authors also observed male preponderance as 10:1. 10 In analysis of 73 cases of symptomatic patent vitellointestinal duct anomalies, there were only 5 cases of patent vitellointestinal duct, and all of them were male infants. 11 Kittle et al also documented patent vitellointestinal duct 4.4 times more in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…There are two options for the surgical resection of the patent vitellointestinal duct: (1) resection of the patent vitellointestinal duct along with wide wedge resection of the ileum and ileal repair; and (2) resection of the patent vitellointestinal duct, adjacent small segment of ileum, and ileoileal anastomosis. [6][7][8]10,13,17 Above surgical procedures can be accomplished through the subumbilical incision, infraumbilical incision, transumbilical approach, or supraumbilical right transverse abdominal incisions. Surgical procedures done through the umbilicus and subumbilical incision carries the best cosmetic results.…”
Section: Patent Vitellointestinal Duct Ghritlahareymentioning
confidence: 99%
See 1 more Smart Citation
“…The omphalomesenteric duct (OMD), also called the vitelline or vitellointestinal duct (VID), is an embryonic structure providing communication from the yolk sac to the midgut during fetal development [ 1 ]. The natural fate of this structure is spontaneous obliteration, where it separates from the intestine during fifth and ninth weeks of gestation [ 2 ]. Failure of its regression results in a spectrum of anomalies including Meckel's diverticulum, patent OMD (POMD), Meckel’s band, omphalomesenteric cysts, umbilical sinus, or umbilical polyp [ 3 ].…”
Section: Introductionmentioning
confidence: 99%